P25 A novel cost-saving approach to the sleep clinic non-attenders with CPAP machines. (2nd December 2011) - Shah, A H; Close, P; Oliver, J; West, S D
Abstract : Introduction: Increasing numbers of patients are diagnosed with Obstructive Sleep Apnoea Syndrome (OSAS) and require Continual Positive Airway Pressure (CPAP) treatment. There is little work following up patients who have received CPAP machines and then default from outpatient review. Contacting these patients may allow their care to be optimised and reclaiming unused machines may enable cost-savings in terms of reuse. Our objective was to establish if Sleep Clinic non-attenders were still using their CPAP machines, and whether a potential cost-saving was achievable from reclamation of CPAP machines. Methods: A search was performed on the Sleep Service CPAP database for patients with OSAS who had defaulted from follow-up for at least 3 years. Administration staff performed phone-based interviews based on a simple proforma, which established the status of patients' CPAP use—active, usage with problems, or no longer using. Sleep Service physiologists contacted the patients having problems with CPAP, to troubleshoot and arrange appointments for review and machine servicing. Arrangements were made for unused CPAP machines to be returned. A cost analysis was based on cost of a CPAP unit and the overtime cost of the administration staff involved in contacting patients. Results: We identified 196 patients who had CPAP machines and had defaulted from follow-up for 3 years or more. Of these, 138 (70%) patients stated they wished to continue CPAP treatment and required out-patient review. There were 58 (30%) patients no longer using CPAP and wanted to discontinue; they were asked to return their CPAP machine or be invoiced. Machines in good condition could be re-used for other patients. Based on unit cost, this could represent savings of up to £10 400. Administration overtime staff costs for this project were £386 (44 h work) and therefore the overall potential cost-saving was £10 014. Conclusions: An active search and contact of non-attenders to Sleep Clinic prescribed CPAP has identified a significant proportion no longer using their CPAP machines. The cost of this search was relatively low and thus cost-savings could be achieved in terms of reclaiming and reusing machines. This may represent an important cost-saving exercise as Sleep services continue to expand.